Virtual material science laboratory manual / Muhammad Nazri Nayan and Mohammad Azizi Abdullah - Nayan, Muhammad Nazri; Abdullah, Mohammad Azizi (2004)
This Virtual Material Science laboratory manual is basically a computer programming project to computerized conventional material science laboratory manual. This indicates that all the experimental scripts can able to be displayed in interactive manner using computer as a platform rather than paper handout. This project considers various aspects in the process of developing the computer program. Start from collecting related theories and experiments involved in the Material Science subject, selection of computer programming language and lastly designing the user interface and display of the program. Progression of this new virtual laboratory manual is also considered in the research. Virtual laboratory manual is a web programming and up to date programming language such as HTML, JavaScript and ASP is implemented to fulfill the needs and requirements of this project. This project can set a new development trend of the virtual laboratory programming project to the faculty.